2019
DOI: 10.2514/1.a34416
|View full text |Cite
|
Sign up to set email alerts
|

Meteor Shower Forecasting in Near-Earth Space

Abstract: NASA's Meteoroid Environment Office (MEO) produces an annual meteor shower forecast in order to help spacecraft operators assess the risk posed by meteoroid streams. Previously, this forecast focused on the International Space Station and therefore reported meteoroid fluxes and enhancement factors at an orbital altitude of 400 km. This paper presents an updated forecast algorithm that has an improved calculation of the flux enhancement produced by showers and can calculate fluxes at any selected Earth or lunar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…MEM specifically models the sporadic component of the meteoroid environment, that is, those meteoroids not affiliated with a meteor shower. For particles <0.5 cm, less than 10% of the net fraction of impactors hitting Earth are from showers (Moorhead et al, 2017). Thus, showers are considered by the authors of MEM to be a minor contributor to spacecraft risk and are not included.…”
Section: Memmentioning
confidence: 99%
“…MEM specifically models the sporadic component of the meteoroid environment, that is, those meteoroids not affiliated with a meteor shower. For particles <0.5 cm, less than 10% of the net fraction of impactors hitting Earth are from showers (Moorhead et al, 2017). Thus, showers are considered by the authors of MEM to be a minor contributor to spacecraft risk and are not included.…”
Section: Memmentioning
confidence: 99%
“…We anticipate that the primary application of our numerical approximations will be in environment models. For instance, the NASA Meteoroid Environment Office (MEO) issues meteor shower forecasts (Moorhead et al 2019b) that have been recently updated to incorporate the Staubach et al (1997) treatment of gravitational focusing. We have found that spacecraft at high altitudes, such as those in geostationary orbit, often pass near the anti-radiant of active meteor showers and were thus predicted to encounter brief but intense spikes in the impactor flux.…”
Section: Meteoroid Environment Modelsmentioning
confidence: 99%
“…Since the beginning of semi-regular operations in December 2018, the GMN recorded a total of ∼ 220, 000 meteors for which orbits were computed (up to mid-2021). Every night-time annual meteor shower of significance for the satellite impact hazard (Moorhead et al 2019) was observed by the GMN over that period.…”
Section: Resultsmentioning
confidence: 99%